Chapter Online Critical Debate Model: Deliberation for the Digital Age - Fuentes Bravo, Claudio (Communication and Philosophical Cultures. Researches and Instruments, 2021)
Through our experience during a large-scale public engagement exercise in Chile we draw conclusions to adapt and improve the Critical Debate Model to an online format. We highlight the importance of epistemic opposition and structured annotation for the execution of debates, while also exploring the possibilities of automated analysis using Natural Language Processing. We conclude by describing how an online version of the Critical Debate Model could be implemented.